The influence of sales promotion on consumers’ store choice - Cunha, S. M. da.; Crespo de Carvalho, J. (5th International Congress Marketing Trends, 2006)
The determinants of consumer’s store choice are complex. Knowing more about store decision should help in addressing practical distribution and marketing problems and improving our understanding of the consume. The present research explores the influence of sales promotion on store choice. This paper presents a conceptual model of the process of assessing a retail format that includes the sales promotion. The objective is to examine: (1) if sales promotion are a store choice criteria, and (2) what type of sales promotion is more important to choose a store. To test the conceptual model is used a sample of hypermarket customers.